‘Dark Tourism’ and the ‘Kitschification’ of 9/11 - Potts, Tracey (Sage, 2012)
This paper aims to interrogate the framing of New York’s Ground Zero as a ‘dark tourist’ destination, with particular reference to the entanglement of notions of kitsch in academic discussions of the events of September 11th 2001. What makes Ground Zero contentious, even scandalous, for many scholars is the presence of a conspicuous commodity culture around the site in the form of tourist souvenirs, leading to accusations of kitschification of memory and the constitution of visitors as ‘tourists of history’. Drawing upon theoretical ideas of Jacques Ranciere, Bruno Latour and W. J. T. Mitchell around image politics, the alignment of kitsch with the figure of the tourist will be questioned, along with the conviction that the so-called ‘teddy-bearification’ of 9/11 threatens the formation of dangerous political subjectivities. In attempting to rid the debates of their default settings, and reliance on essentialist notions of kitsch, it is hoped that that the way will be cleared for the sociological, ethnographic and empirical work necessary to considering the cultural and political significance of the Ground Zero souvenir economy.